Prevention of Congenital Transmission of Malaria in Sub-Saharan African Countries: Challenges and Implications for Health System Strengthening. (22nd September 2011) - Osungbade, Kayode O.; Oladunjoye, Olubunmi O.
Abstract : Objectives . Review of burden of congenital transmission of malaria, challenges of preventive measures, and implications for health system strengthening in sub-Saharan Africa. Methods . Literature from Pubmed (MEDLINE), Biomed central, Google Scholar, and Cochrane Database were reviewed. Results . The prevalence of congenital malaria in sub-Saharan Africa ranges from 0 to 23%. Diagnosis and existing preventive measures are constantly hindered by weak health systems and sociocultural issues. WHO strategic framework for prevention: intermittent preventive therapy (IPT), insecticide-treated nets (ITNs), and case management of malaria illness and anaemia remain highly promising; though, specific interventions are required to strengthen the health systems in order to improve the effectiveness of these measures. Conclusion . Congenital malaria remains a public health burden in sub-Saharan Africa. Overcoming the challenges of the preventive measures hinges on the ability of national governments and development partners in responding to the weak health systems.